Forensic aspects of the investigation of money laundering through cryptocurrency transactions - Popovych , Myroslav (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The article examines the peculiarities of the investigation of criminal offenses related to money laundering through cryptocurrency transactions. Crypto assets and types of offenses related to cryptocurrency are analyzed. The discovery and investigation of the first cryptocurrency bribe in the history of Ukraine is described in detail. The Blockchain technology, which is the basis of cryptocurrencies and makes it easier for law enforcement officers to track virtual money, is considered. It is clarified what is the complexity of the pre-trial investigation of this category of criminal cases and the peculiarities of bringing the guilty persons to justice, namely, the establishment of a connection between, on the one hand, transactions and addresses, and on the other hand, individuals in the real world. In other words, identifying potentially criminal agreements, as well as the criminals who entered into them. It is emphasized that methods that can be used by law enforcement to enhance the apparent anonymity of cryptocurrencies and link transactions and addresses to individuals suspected of committing a criminal offense and money laundering are highlighted. The Law of Ukraine «On Prevention and Counteraction to Legalization (Laundering) of Proceeds from Crime, Financing of Terrorism and Financing of Proliferation of Weapons of Mass Destruction» has been studied. The necessity to expand the capabilities for detecting signs of legalization and investigating criminal offenses related to money laundering through cryptocurrency transactions is emphasized. Extensive regulation and full use of existing laws are needed – to ensure that crypto assets are treated like any other assets for the purpose of monitoring, enforcement, and asset recovery in the context of anti-money laundering. It is also worth emphasizing its use of blockchain to undermine organized crime – given that blockchain offers many opportunities for investigating and preventing criminal offenses and money laundering schemes, intelligence gathering, and freezing and confiscating illegal assets.